Seasonal variation in suicide: age group and summer effects in the United States (2015–2020) - Samantha To; Erick Messias; Laura Burch; John Chibnall (BMC Psychiatry)
Abstract Background Suicide is a global public health concern that affects more than 700,000 people globally every year. Seasonal variation in suicide rates is a phenomenon that has been well-documented, but recent data on the seasonality of suicide within specific age groups and sex in the United States remains less well understood. Methods Publicly available data on monthly suicides was obtained from the Underlying Cause of Death database, CDC WONDER, from 2015–2020. The incidence of summer suicides, from June, July and August, for two groups, 15–24 and ages 25 + , was calculated and a two-sided test was performed. Seasonal Decomposition analysis was performed and time series created from 2015–2020 for every age group then converted into Trend, Seasonality, and Residual respectively. Results For Americans ages 15–24, the highest spike in suicides was in autumn, September–October, with a trough in June. This is the only age group in which this occurred, differing from previous understanding of the seasonality of suicide in the literature. With all other age groups (25–34, 35–44, 45–54, 55–64, 65–74, 75 +) there was a consistent pattern of a peak in late spring/early summer, a small peak in fall, and a trough in late winter. Conclusions There is a seasonal variation in suicide deaths in the United States with the youngest group, ages 15–24, presenting a different pattern compared to other ages. There were no significant differences in suicide seasonality by sex.